Human Resources Competence in The Indonesian National Armed Forces and Ministry/ Non-Ministry Government Institutions - Syabilarrasyad, Syabilarrasyad; Irianto, Jusuf; Suhariadi, Fendy (Devotion : Journal of Research and Community Service, 2023)
This study aims to identify policies and practices for developing human resource competencies in TNI (Indonesian National Armed Forces) organizations and Ministries/Non-Ministerial Government Agencies. This study uses a qualitative approach with a multiple case study design. The research subjects were two organizations, namely the TNI and Ministries/Non-Ministerial Government Agencies. Data collection was carried out through literature studies. The collected data were then analyzed using thematic analysis techniques. The results of the analysis show that the TNI organization and the Ministries/Non-Ministry Government Agencies show ideas about the concept of career planning that can solve the problem of stagnation of positions in order to make the TNI Transformation successful in the future. Therefore, TNI organizations and Ministries/Non-ministerial Government Agencies need to continue to develop appropriate policies and practices in developing human resource competencies, as well as considering the constraints that occur. In the context of globalization and increasingly fierce competition, developing human resource competencies in government organizations is very important to support the achievement of organizational goals and improve the quality of public services.